Exploring physical literacy in children aged 8 to 12 years old: a cross-cultural comparison between China and Greece - Ming Hui Li; Vasiliki Kaioglou; Rui Si Ma; Siu Ming Choi; Fotini Venetsanou; Raymond Kim Wai Sum (BMC Public Health, 2022)
Abstract Background The concept of physical literacy (PL) has been advocated as a crucial determinant for increasing the quality and quantity of movement and physical activity (PA). Children’s PL has been rarely compared across countries, although it has shown low levels in many countries. This study aimed to explore and compare children’s PL from China and Greece. Methods A total of 327 Chinese (47.1% boys) and 295 Greek children (48.1% boys) aged 8 to 12 years participated in this study. Children’s PL was objectively assessed by the Chinese and Greek version of the Canadian Assessment of Physical Literacy, 2nd edition, which consists of four domains: Daily Behavior, Physical Competence, Motivation and Confidence, and Knowledge. and Understanding. Univariate analysis of covariance (ANCOVA) and multivariate analysis of covariance (MANCOVA) on total PL and domain scores were conducted in both countries, respectively. Results MANOVA revealed significant differences in total PL and distribution scores between two countries (Pillais’ trace = 0.260, F = 53.855, p < 0.001, η2 = 0.260), with Greek children scoring better than Chinese. Nevertheless, most children failed to present an adequate PL level as they were mostly in the “progressing” stage. The chi-square denoted that the distribution of Chinese and Greek participants across the CAPL-2 interpretive categories was statistically different for total PL (χ2 [3] = 18.726, p < 0.001, Cramer’s V = 0.174), with more Greek children being classified as “achieving” and “excelling”. Conclusions The variance between Chinese and Greek children may be attributed to cultural differences in the context of PA, such as PE policies and settings. The relatively low level of PL shown in both countries echoes the global trend of the declining PA among children, with an increasing amount of their time spent in a sedentary lifestyle. These findings highlight the need to consider children’s cultural factors and pedagogical strategies in terms of developing their PL. Future research is required to explore the impact of cultural background on PL development among children and appropriate strategies to migrate their influence.